2007
DOI: 10.1258/096914107781261927
|View full text |Cite
|
Sign up to set email alerts
|

An advance notification letter increases participation in colorectal cancer screening

Abstract: Objectives: To determine the impact of novel invitation strategies on population participation in faecal immunochemical test (FIT)-based colorectal cancer (CRC) screening. Setting A community screening programme in Adelaide, South Australia. Methods: In total, 2400 people aged 50–74 years were randomly allocated to one of four CRC screening invitation strategies: (a) Control: standard invitation-to-screen letter explaining risk of CRC and the concept, value and method of screening; (b) Risk: invitation with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 21 publications
7
109
2
2
Order By: Relevance
“…Consistent with other studies in Australia (Cole, Smith, Wilson, Turnbull, Esterman, & Young, 2007;Cole, Young, & Byrne, 2002;Zajac, Whibley, Cole, Byrne, Guy, Morcom et al, 2010) and internationally (Brouse et al, 2003;Damery, Clifford, & Wilson, 2010;Federici, Rossi, Bartolozzi, Farchi, Borgia, & Guastcchi, 2006;Ferreira, Dolan, Fitzgibbon, Davis, Gorby, Ladewski et al, 2005;Klabunde, Frame, Meadow, Jones, Nadel, & Vernon, 2003;Myers, Sifri, Hyslop, Rosenthal, Vernon, Cocroft et al, 2007;Rossi et al, 2005;Vernon, 1997), our study also revealed that doctor's recommendation and endorsement is one of the strongest predictors of CRC screening. Studies in the UK which use sigmoidoscopy as the method of CRC screening also highlight the importance of GP endorsement and recommendation (Brotherstone, Vance, Edwards, Miles, Robb, Evans et al, 2007;McCaffery, Borril, Williamson, Taylor, Sutton, Atkin et al, 2001;Power, Van Jaarsveld, McCaffery, Miles, Atkin, & Wardle, 2008;Robb, Power, Kralj-Hans, Edwards, Vance, Atkin et al, 2010;Sutton, Wardle, Taylor, McCaffery, Williamson, Edwards et al, 2000), although the relevance of these studies may be questioned due to the different type of CRC screening test used.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies in Australia (Cole, Smith, Wilson, Turnbull, Esterman, & Young, 2007;Cole, Young, & Byrne, 2002;Zajac, Whibley, Cole, Byrne, Guy, Morcom et al, 2010) and internationally (Brouse et al, 2003;Damery, Clifford, & Wilson, 2010;Federici, Rossi, Bartolozzi, Farchi, Borgia, & Guastcchi, 2006;Ferreira, Dolan, Fitzgibbon, Davis, Gorby, Ladewski et al, 2005;Klabunde, Frame, Meadow, Jones, Nadel, & Vernon, 2003;Myers, Sifri, Hyslop, Rosenthal, Vernon, Cocroft et al, 2007;Rossi et al, 2005;Vernon, 1997), our study also revealed that doctor's recommendation and endorsement is one of the strongest predictors of CRC screening. Studies in the UK which use sigmoidoscopy as the method of CRC screening also highlight the importance of GP endorsement and recommendation (Brotherstone, Vance, Edwards, Miles, Robb, Evans et al, 2007;McCaffery, Borril, Williamson, Taylor, Sutton, Atkin et al, 2001;Power, Van Jaarsveld, McCaffery, Miles, Atkin, & Wardle, 2008;Robb, Power, Kralj-Hans, Edwards, Vance, Atkin et al, 2010;Sutton, Wardle, Taylor, McCaffery, Williamson, Edwards et al, 2000), although the relevance of these studies may be questioned due to the different type of CRC screening test used.…”
Section: Discussionsupporting
confidence: 92%
“…Our national trial of GPE significantly increased uptake overall. The effect size was smaller than in many previous studies, 36,196,216,217 but this was probably because most of those had used letters directly from the GP or had an individual GP's signature on the letter. In the NHS BCSP, all invitation letters come from the hubs; therefore, the only practical option was to include a banner noting that the individual's general practice supported the programme, but without individual GPs' names or signatures.…”
Section: Discussioncontrasting
confidence: 66%
“…68 part to the health belief model, 66 with the letter acting as a cue and increasing preparedness to participate in screening. In an Australian study, 6 a so-called advanced notification letter ahead of the standard invitation for bowel cancer screening was associated with a 25% greater uptake than the standard invitation alone. These authors cited the transtheoretical model in suggesting that simply increasing awareness may move people from contemplating (screening) to action.…”
Section: Strengths and Weaknessmentioning
confidence: 97%
“…Therefore, we used a prior focus group of young women to inform the development of a more concise leaflet that specifically addressed the key issues highlighted. Indeed, pre-notification for colorectal screening has been associated with a small but significant increase in uptake in both Scotland 6 and Australia. 7 Online booking has become the norm for many activities and we felt that this would help overcome any inconvenience engendered by the need to book an appointment to attend for cervical screening.…”
Section: Considerations In Designing a Study To Address Non-participamentioning
confidence: 99%